Palladium‐Catalyzed Formal Cross‐Coupling of Diaryl Ethers with Amines: Slicing the 4‐O‐5 Linkage in Lignin Models - Zeng, Huiying; Cao, Dawei; Qiu, Zihang; Li, Chao‐Jun (Angewandte Chemie International Edition, 2018)
Lignin is the second most abundant organic matter on Earth, and is an underutilized renewable source for valuable aromatic chemicals. For future sustainable production of aromatic compounds, it is highly desirable to convert lignin into value‐added platform chemicals instead of using fossil‐based resources. Lignins are aromatic polymers linked by three types of ether bonds (α‐O‐4, β‐O‐4, and 4‐O‐5 linkages) and other C−C bonds. Among the ether bonds, the bond dissociation energy of the 4‐O‐5 linkage is the highest and the most challenging to cleave. To date, 4‐O‐5 ether linkage model compounds have been cleaved to obtain phenol, cyclohexane, cyclohexanone, and cyclohexanol. The first example of direct formal cross‐coupling of diaryl ether 4‐O‐5 linkage models with amines is reported, in which dual C(Ar)−O bond cleavages form valuable nitrogen‐containing derivatives. From waste to value: A strategy for converting renewable lignin biomass into value‐added nitrogen‐containing chemicals is reported. Model compounds of lignin containing a 4‐O‐5 linker were cross‐coupled with amines by dual C(Ar)−O bond cleavages to generate valuable nitrogen‐containing derivatives.